Time power - Hobbs, Charles R (Harper & Row, 1987)
This book shows us how to: align our personal goals with our job duties; increase personal productivity; handle priorities by learning the difference between vital and urgent; cope with demands; delegate effectively; reduce crisis management; procastinate effectively; identify and eliminate time wasters; anticipate and control events; and find extra hours in the day for our personal life.